Regulation of TADF by Internal and External Heavy Atom Effect in D‐A MOF for Heterocrystal based Temperature‐Compensated Photonic Device - Zhang, Bo; Li, Chang‐Tai; Wang, Han‐Yu; Fang, Han; Feng, Rui; Yu, Mei‐Hui; Li, Wei; Chang, Ze; Bu, Xian‐He (Angewandte Chemie International Edition, 2025)
The application of temperature‐compensated photonic device is hampered by poor accuracy and overly simplistic functions of propagation in photonic integrated circuits (PICs) field. Herein, we report a new library of donor‐acceptor metal–organic framework (D−A MOF) with thermally activated delayed fluorescence (TADF) and the fabricating of temperature‐compensated photonic device by virtue of the unique temperature response character of TADF emitters. Highly tunable through‐space charge transfer (TSCT) of TADF was realized within the D−A MOFs through a novel strategy that synergistically combines the internal heavy atom effect (HAE) with an external HAE, induced by the incorporation of heavy atoms into different components, achieving the regulable photophysical indicators including adjustable PL wavelength (534 to 592 nm) and surging quantum yield (5.02 %–47.39 %). Further investigation of the impact of external HAE on TADF was conducted through crystal structures and Hirshfeld surface plots of four D−A regimes featuring substituent‐based linkers. Notably, temperature‐compensated photonic device based on heterocrystal was fabricated through integrating D−A MOFs with contrary temperature response. The emission signal output of the heterojunction remained nearly stable in 215 K to 295 K range, highlighting the promising potential application of TADF D−A MOF featuring sensitive temperature response in PICs field. Facilely tunable through‐space charge transfer thermally activated delayed fluorescence (TADF) was realized by synergy of internal and external heavy atom effect induced by decorated ‐Br on different components in donor‐acceptor metal–organic frameworks (D−A MOFs). Photonic temperature compensated device based on heterocrystal was fabricated through integrating D−A MOFs with contrary tendency of temperature‐dependent emission intensity, indicating a potential paradigm in photonic integrated circuits (PICs).